Place navigation in rats with unilateral tetrodotoxin inactivation of the dorsal hippocampus: place but not procedural learning can be lateralized to one hippocampus - Fenton, A A; Bures, J (Behavioral neuroscience, 1993)
Lateralization of the Morris water maze task was examined by injecting 5 ng of tetrodotoxin (TTX) into one dorsal hippocampus (HPC) of chronically cannulated rats (n = 20). The task, acquired (A) during unilateral HPC block, was retrieved (R) during TTX blockade of the ipsi- (I) or contralateral (C) HPC. Escape latencies (in seconds) at 3 levels of acquisition and in the first 4-trial block of I or C retrieval suggest lateralization was absent after the first block (A = 49, I = 40, C = 44), partial after training to an efficient search strategy (A = 6, I = 9, C = 14), and complete after overtraining to goal-directed escape (A = 4, I = 4, C = 12), as further indicated by comparisons of A vs. R behavior and probe trials. The analyses also indicate that (a) HPC contributes to the acquisition but is unnecessary for retrieval of the procedural engram, (b) overtrained learning with one HPC or intact brain is similar, and (c) there is no left-right hemispheric specialization for place learning.
Keywords: Escape Reaction; Animals; hipokampus; Brain Mapping; Orientation; rozpomínání; úniková reakce; orientace; Mental Recall; mapování mozku; Dominance, Cerebral; diskriminační učení; Male; krysa rodu Rattus; Hippocampus; zvířata; mužské pohlaví; dominance mozková; Discrimination Learning; Rats